Splice site selection dominates over poly(A) site choice in RNA production from complex adenovirus transcription units. - Adami, G (1988)
The adenovirus late genes are organized in a complex transcription unit in which the production of multiple RNAs is controlled by specific RNA processing events. Adding to the complexity is the fact that the early E3 transcription unit is wholly contained within the late transcription unit. Within this overlapping region there are splicing events and poly(A) site choices specific to each transcription unit. Early in infection, there is near exclusive use of the E3 splice sites with little L4 poly(A) site use whereas the reverse is true late in infection. Using a plasmid containing an intact E3 transcription unit, we demonstrate that the L4 poly(A) site, located in the first E3 intron, is not used either in a mock-infected cell or a late infected cell; nor is it used if the same transcription unit is driven by the major late promoter. In addition, the nature of the poly(A) site appeared to be unimportant since the E3 poly(A) site was also not used in the intron if inserted in place of the L4 poly(A) site. Thus, splice site selection appears to dominate over poly(A) site choice. This conclusion was confirmed by the observation that deletion of either the E3 splice donor (5'ss) or the E3 splice acceptor (3'ss) allowed the use of the L4 poly(A) site. Finally, the L4 poly(A) site within the E3 intron was also used when additional sequence, including splicing signals from the L4 region and the tripartite leader, was inserted between the promoter and the E3 processing sites. It appears that splicing is the dominant event in governing production of E3/L4 RNAs.